Factors that influenced mental health among students in UiTM Seremban / Mohammad Al Hakim Azman and Luqman Hakim Mohd Zol - Azman, Mohammad Al Hakim; Mohd Zol, Luqman Hakim (2022)
The main aim of this research paper is to study the Factors That Influenced Student Mental Health Among UiTM Seremban.3. The problem statement relies on the understanding of how this factor influenced the behaviors and mental of the student itself. To completely understand the differing views of the students surrounding this issue, it was deemed crucial to investigate the viewpoints of the factor that contribute to the student mental health such as academic factors, family environment, financial situation, and healthy lifestyle It was founded that most of the respondents or the students within UiTM Seremban 3 are lack in the knowledge that these issues seem most of them are affected with the mental health issues. The research paper also provides and suggested many ways for how the universities and social clubs to encourage the students to get engaged to reduce mental health issues in the future.